MORAL IMPERIALISM AND CHILDREN’S AUTONOMY IN CLINICAL TRIALS FOR COVID-19 - Assis de Abreu, Kamila (2024)
This research consists of an unprecedented documentary analysis that aimed to analyze the process of moral and legal imperialism of the European Union and the United States on the Brazilian population regarding bioethical principles, especially from the perspective of children's autonomy. For theoretical contextualization, the phenomenon of autonomy was discussed from a Western biopolitical perspective, identifying the main normative and political influences in Brazil. It concludes by the need for decolonization, with the implementation of the Bioethics of Intervention and Bioethics of Protection, as a bet for a post-Western reality that is fair and appropriate to the Brazilian reality, as well as greater biopolitical participation of infants.